Preparation and partial pharmacodynamic studies of luliconazole ethosomes. (28th February 2022) - Lin, Biwen; Wang, Wenjuan; Ba, Wei; Li, Hengjin; Fan, Jianfeng
Abstract: As a drug carrier, ethosome is found to be efficient in delivering drug to the deep skin layers through stratum corneum, and the purpose of this paper is to develop luridazole ethosomes acting as an optimal choice for transdermal antifungal drugs. The luliconazole ethosomes were prepared by thin‐film hydration, and evaluated for morphology, size, entrapment efficiency (EE), stability and deformability. In vitro, the transdermal experiment was performed on excised rat skin by Franz diffusion cell, and minimum inhibitory concentration (MIC) was applied to determine antifungal activity. In vivo, the irritation of luliconazole ethosomes was also observed in rats. The luliconazole ethosomes were prepared with 5% (w/v) lecithin, 45% (v/v) ethanol and 8‐min ultrasound, and characterised with small and uniform particle size, high EE of about 70%. These ethosomes possessed good deformability, were stable and affected by light and high temperature. The cumulative amount permeated of different dosage forms at 48 h from high to low was: ethosome > ointment > liposome > hydroalcoholic solution ( p < 0.05), and the sum of the luliconazole retention of skin from high to low at 48 h was: ethosome/ointment > liposome > hydroalcoholic solution ( p < 0.05). In the antifungal experiment, the MICs from high to low were: hydroalcoholic solution > liposome > ethosome ( p < 0.05), and Trichoderma was more sensitive to luliconazole than Candida. There was no skin irritation observed after treatment of luliconazole ethosomes. The luliconazole ethosomes are firstly prepared in our study, which have little stimulation, better permeation effect and antifungal activity, offering a new perspective for choosing clinical antifungal drugs in the Department of Dermatology.